Trauma Emosional yang Dialami Masyarakat Banjar Pasca Peristiwa Jum'at Kelabu - Rosalina, Rosalina; Prawitasari, Melisa; Rochgiyanti, Rochgiyanti; Anis, Mohamad Zaenal Arifin (Lambung Mangkurat University, 2022)
The Gray Friday incident, May 23, 1997, which occurred in the city of Banjarmasin, was a conflict event of the election campaign riots that occurred during the New Order era. This incident caused great losses, both material and non-material. Looting, arson, vandalism was carried out by the masses, causing many casualties. This riot had many impacts in various aspects, one of which was the impact on the psychological aspect in the form of emotional trauma. This study aims to determine the chronology of the events of Friday Gray and the psychological impact on the Banjar community. The method used in this study uses the historical method which has four stages, namely heuristics, criticism, interpretation and historiography. The first stage is heuristics or primary and secondary data collection. Primary data was obtained through interviews with the Banjar people who experienced the Gray Friday incident. Secondary data were obtained through books, newspapers, scientific journals, articles on the internet and direct observation of the research. After getting the data, the next stage is criticism, both internal criticism and external criticism. The data that has been criticized then goes to the Interpretation stage and ends with the historiography or writing stage. The results showed that the emotional trauma experienced by the people of Banjar included three emotions, namely fear, sadness, and hatred. The emotional trauma after the Gray Friday shook the psyche of the Banjar community so that it interfered with the daily activities of the Banjar community, but they have tried to recover from the trauma.